Teachers' Perceptions of Teaching English Language to Young Learners in Libyan Primary Schools in Al-Marj region - Senussi Orafi,; Hanan Idris, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
This study aims to establish the opinions of teachers in the Al-Marj region of Libya regarding the teaching of the English language to young learners in primary schools. The researchers adopted semi-structured interviews as a data collection tool to provide insight into three teachers’ perceptions, attitudes and experiences relating to English language instruction. The findings indicate that teachers generally hold positive attitudes regarding the importance of teaching the English language to young learners. However, the analyses reveal several influential factors which affect the teaching process. These factors include large class sizes, limited instructional time, pressure from inspectors to complete the syllabus, a lack of resources (especially textbooks), students' varying levels of English proficiency, and inadequate support from parents and the community. The study suggests that addressing these factors could help to improve the quality of English language education for young learners in Libyan primary schools. By recognising and addressing these challenges, stakeholders can work to improve the quality of English language education for both teachers and young learners in Libyan primary schools.